1985
DOI: 10.1161/01.cir.72.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic tissue characterization: detection of acute myocardial ischemia in dogs.

Abstract: Ultrasonic tissue characterization is a new area of investigation in the field of cardiac ultrasound. The amplitude and frequency of the ultrasound signal are normally altered as the signal penetrates through tissue. It is assumed that the amplitude distribution and frequency shift of diseased or edematous tissue are different than those of normal tissue. A statistical approach to the analysis of the unprocessed radiofrequency signal in the amplitude domain was used to study the effect of acute myocardial isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This would derive from a temporal PSF whose square is given by (23) WAGNER et al Page 11 The Fourier transform of this function is a triangle and its square is the parabolic shape whose right half is given in Fig. 7.…”
Section: Correlations Between Images To Be Frequency Compoundedmentioning
confidence: 99%
See 2 more Smart Citations
“…This would derive from a temporal PSF whose square is given by (23) WAGNER et al Page 11 The Fourier transform of this function is a triangle and its square is the parabolic shape whose right half is given in Fig. 7.…”
Section: Correlations Between Images To Be Frequency Compoundedmentioning
confidence: 99%
“…From the preceding discussion it would appear that either the speckle contrast (or its inverse, SNR o -see, e.g., [23]), or the speckle cell size, would serve as a tissue signature corresponding to the value of the specular to diffuse scattering ratio r. This is only true, however, when there are very many diffuse scatterers per resolution cell. We now consider the case where this number decreases toward zero.…”
Section: A Addition Of Coherent Scattermentioning
confidence: 99%
See 1 more Smart Citation
“…CVIBS is blunted promptly by ischemia and is augmented after reperfusion in animals and humans. 25,[29][30][31] Lin, et al 32) found that the cut-off value was 2.0 db in predicting reversible myocardial dyssynergy after revascularization. Vitale, et al 33) showed that the maximum-minimum difference of the integrated backscatter (CVIBS) was reduced significantly by stress in the septum (4.6 ± 0.9 versus 2.7 ± 0.8) (difference, 1.9 db).…”
Section: A B Discussionmentioning
confidence: 99%
“…This implies that IB is a measure of the mean reflected ultrasonic energy from a particular region of tissue [4] . The aspect of myocardial tissue characterization which has aroused most interest has been the potential predictive value of the cyclic variation (CV) of IB for determining myocardial viability, initially described in vivo in animal models [5][6][7][8][9] . This work has also been reproduced in the clinical setting [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%